KONTRIBUSI BAITUL HIKMAH DALAM PERKEMBANGAN KEILMUAN DAN PENDIDIKAN PADA MASA DINASTI ABBASIYAH - Kamalia, Shafa; Dzulkifli Hadi Imawan; Imawan, Dzulkifli Hadi (MADINAH, 2025)
The Abbasid dynasty reached its peak in education with the establishment of Baitul Hikmah in 830 AD as an integrated intellectual center. This institution became a symbol of the progress of Islamic civilization through the movement of translation, research, and scientific development. This research aims to analyze the history, role, and impact of Baitul Hikmah as a multifunctional educational institution that encouraged scientific transformation during the Abbasid period. This research uses a descriptive qualitative method with a library research approach, which examines literature sources such as books, journals, and documents related to Baitul Hikmah. The results of this study show that Baitul Hikmah acted as a translation center, academy, and library that gave birth to prominent Muslim scientists such as al-Khwarizmi, Ibn Sina, Ibn Rushd, and various other figures. This institution also triggered the establishment of public libraries in various Islamic cities. In addition, Baitul Hikmah became the foundation of the transformation of Islamic education through cross-cultural scientific integration. Its contributions not only impacted the Abbasid period, but also inspired the development of modern education.